2019
DOI: 10.1038/s42255-019-0063-6
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 controls iron homoeostasis in haemochromatosis and thalassaemia via Bmp6 and hepcidin

Abstract: Iron is critical for life but toxic in excess because of iron-catalysed formation of pro-oxidants that cause tissue damage in a range of disorders. The Nrf2 transcription factor orchestrates cell-intrinsic protective antioxidant responses, and the peptide hormone hepcidin maintains systemic iron homeostasis, but is pathophysiologically decreased in haemochromatosis and beta-thalassaemia. Here, we show that Nrf2 is activated by iron-induced, mitochondria-derived pro-oxidants and drives Bmp6 expression in liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
111
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 57 publications
5
111
3
Order By: Relevance
“…[12][13][14] Hepcidin expression is modulated by the BMP/SMAD signaling pathway: binding of bone morphogenetic proteins (BMPs) to BMP receptors in the membrane of hepatocytes causes phosphorylation of cytosolic SMADs (SMAD1/5/8) that translocate to the nucleus complexed with SMAD4 to activate the transcription of target genes, including hepcidin (HAMP). [15][16][17] This pathway is activated in response to iron via BMP6 18,19 and by BMP2 independently of BMP6. 20 Hepcidin suppression during erythropoiesis is mediated at least in part by erythroferrone (ERFE), a protein synthesized in erythroblasts in response to erythropoietin (EPO), downstream of JAK2-STAT5 signaling.…”
mentioning
confidence: 99%
“…[12][13][14] Hepcidin expression is modulated by the BMP/SMAD signaling pathway: binding of bone morphogenetic proteins (BMPs) to BMP receptors in the membrane of hepatocytes causes phosphorylation of cytosolic SMADs (SMAD1/5/8) that translocate to the nucleus complexed with SMAD4 to activate the transcription of target genes, including hepcidin (HAMP). [15][16][17] This pathway is activated in response to iron via BMP6 18,19 and by BMP2 independently of BMP6. 20 Hepcidin suppression during erythropoiesis is mediated at least in part by erythroferrone (ERFE), a protein synthesized in erythroblasts in response to erythropoietin (EPO), downstream of JAK2-STAT5 signaling.…”
mentioning
confidence: 99%
“…Indeed, macrophages, in addition to their key role in the initiation and sustainability of the inflammatory response, have a central role in the management of iron homeostasis. This link between inflammatory response, pathogen defense and iron homeostasis control has already been documented [53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 70%
“…However, the exact mechanism underlying the regulation of BMP6 gene expression in liver is largely unknown. In a recent study, the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) was reported to regulate hepatic BMP6 expression in response to iron by directly binding the BMP6 gene promoter [ 36 ]. Here, we show that orphan nuclear receptor ERRγ transcriptionally regulates hepatic BMP6 expression by directly binding the ERRE motif in the BMP6 gene promoter, in response to IL-6 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…NPCs include hepatic stellate cells, Kupffer cells and liver sinusoidal epithelial cells. Hepatic BMP6 production was reported from NPCs in several reports [ 36 , 38 , 39 ]. In particular, it was reported that BMP6 basal expression was confined to NPCs, namely HSCs and KCs, and treatment with TGF-β1 increased BMP6 gene expression in HSCs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%